PREPARATION, CHARACTERIZATION, AND EVALUATION OF THE PHOTOCATALYTIC EFFECT OF α-Fe2O3/SAPO-34 IN THE ELIMINATION PROCESS OF THE ANTI-CANCER DRUG DOXORUBICIN FROM AQUEOUS SOLUTION - BIGTAN, Mohammad Hosein; MAHANPOOR, Kazem (Studia Universitatis Babeș-Bolyai Chemia, 2017)
In this investigation, α-Fe2O3/SAPO-34 nano-structure were synthesized and characterized by XRD, SEM and FT-IR techniques. Morphologically, the shape of α-Fe2O3/SAPO-34 nanoparticles is close to spherical nanoparticles with an average particle size of 93 nm determined by Debye-Scherrer equation. The photocatalytic activity of α-Fe2O3/SAPO-34 nanostructure was investigated through the degradation of doxorubicin, an anti-cancer drug using a batch reactor under UV-C irradiation and H2O2 as oxidant. The effect of various factors including drug concentration, catalyst dosage, pH and H2O2 concentration on the degradation yield were investigated. The results showed that optimum conditions were: Initial concentration of DOX = 20 ppm, pH = 8, amount of α-Fe2O3/SAPO-34 = 150 mg/L, and H2O2 concentration 4 mol/L.